Biosurfactants of Rhodococcus erythropolis IMV Ас-5017: synthesis intensification and practical application - Pirog, Tatiana; Sofіlkanich (Morozova), Anna; Shulyakova, Mariya; Shevchuk, Tetiana (My University, 2013)
Intensification of the surfactant synthesis by Rhodococcus erythropolis IMV Ac-5017 on different substrates, including industrial waste, as well as the use of surfactant preparations for oil degradation were studied. It was established that the addition of fumarate (0.2 %) and citrate (0.1 %) into the medium with ethanol, n-hexadecane, or glycerol (1–2 %) was accompanied by an increase of conditional surfactant concentration by 1.5–1.7 times compared to the indexes in the medium without organic acids. The intensification of surfactant synthesis in the presence of fumarate and citrate is caused by the increased activity of isocitrate lyase (by 1.2–15-fold) and enzymes of the surfactant biosynthesis (by 2–4.8-fold) compared to their activity in the medium without precursors. The possibility of surfactant synthesis intensification (by 3–4-fold) while cultivating of R. erythropolis IMV Ac-5017 in the medium with oil containing substrates (2 %) and glucose (0.1 %) was shown. The introduction of 0.01 mM Cu2+ in the exponential growth phase of strain IMV Ac-5017 in the medium with ethanol accompanied by the increasing conditional surfactant concentration by 1.9 times. The highly efficient remediation (92–95 %) of oil (2–2.6 g/L) and Cu2+ polluted water after treatment with surfactant preparations (native cultural liquid) at low concentrations (5 %) was determined.
Keywords: Rhodococcus erythropolis IMB Ac-5017; поверхнево-активні речовини; інтенсифікація біосинтезу; поверхностно-активные вещества; интенсификация биосинтеза; surfactant; biosynthesis intensification; кафедра біотехнології і мікробіології